Juggling digitization and technostress: The case of alert fatigues in the patient care system implementation. Issue 4 (December 2015) - Khuntia, Jiban; Tanniru, Mohan; Weiner, Jack
Abstract: Policy mandates and business benefits are propelling hospitals to implement several decision support systems that can help nurses to aid in clinical care decisions. These systems can plausibly reduce errors and provide care by offering real-time alerts about possible adverse reactions. But nurses often suffer "alert fatigue" caused by excessive numbers of warnings within the hospital while providing care. As a result, they may pay less attention to or even ignore some vital alerts, thus limiting these systems׳ effectiveness. In this study, we explore how implementation of an intelligent care system in a hospital with the objective of implementing several decision support systems inadvertently led to a set of alert fatigues. Our analysis of fatigue related technostress suggests a change in management strategy that involves synchronization of people, technology and policies, and is in support of patient care. Highlights: Technology-induced care. Alert fatigue on care staff. Policy impact on stress.